Normative og metodiske vinkler på "arbejde" som et sundhedsøkonomisk begreb - Brock, Steen; Christensen, Bo Allesøe (Tidsskrift for Forskning i Sygdom og Samfund, 2012)
This paper begins by recounting important phases in the development of the concept of labour. Then the Capability Approach to welfare economy, by Amartya Sen, is presented as is the direction of socio-psychology called Positioning Theory. Accordingly, the paper advocates a way in which to assess the economy of health programs as a cornerstone within Public Health Strategies to the effect that the concept of labour is important in this context. All way through, the paper examines the inescapable gap between a professionalized authoritative viewpoint on labour and an authentic perspective thereupon.